Combination of multivariate volatility forecasts - Alessandra Amendola; Giuseppe Storti (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
This paper proposes a novel approach to the combination of conditional covariance matrix forecasts based on the use of the Generalized Method of Moments (GMM). It is shown how the procedure can be generalized to deal with large dimensional systems by means of a two-step strategy. The finite sample properties of the GMM estimator of the combination weights are investigated by Monte Carlo simulations. Finally, in order to give an appraisal of the economic implications of the combined volatility predictor, the results of an application to tactical asset allocation are presented.
Keywords: C52; C53; C32; G11; G17; 330; Multivariate GARCH; forecast combination; GMM; portfolio optimization; Volatilität; Prognoseverfahren; Momentenmethode; Multivariate Analyse; ARCH-Modell; Portfolio-Management; Theorie